Tissue and serum levels of substance P in trichodynia of androgenetic alopecia patients - Yasser M. Gohary; Olfat G. Shaker; Lina A. Elshimy; Shimaa T. Osman (Journal of the Egyptian Women’s Dermatologic Society)
Background Trichodynia or hair pain refers to the painful sensation occurring in the hair and or scalp in the setting of hair shedding. It has been reported mainly in association with telogen effluvium and androgenetic alopecia (AGA). Recently, trichodynia cases have been growing in numbers. Several theories have been proposed to explain the pathogenesis of trichodynia, suggesting a major role for substance P (SP) accompanied by perifollicular inflammation. Objective To assess tissue and serum levels of SP in trichodynia occurring in AGA patients. Patients and methods This is a case–control study that included 35 patients of trichodynia in AGA as well as 35 age-matched and sex-matched healthy participants included as controls. The diagnosis was made by clinical, trichoscopic examination, and scalp biopsy. Tissue and serum levels of SP were measured using the enzyme-linked immunoassay technique. Results The mean tissue levels of SP were significantly higher in patients (448.11±241.24 pg/g), than in controls (75.78±11.81 pg/g) (P<0.0001). The mean serum levels of SP were significantly higher in patients (325.09±218.43 pg/ml), than in controls (171.06±42.19 pg/ml) (P=0.0002). The mean levels of SP in the tissue of patients were significantly higher among those with positive tenderness by examination (322.62±64.11123) compared to those with no tenderness (553.78±284.12157) (P=0.003). The mean levels of SP in the tissue of AGA patients were significantly higher in the group who reported a diffuse distribution of trichodynia (553.78±284.12) than in patients with localized trichodynia (322.62±64.11) (P=0.028). Conclusion An increase of SP levels in tissue and serum of trichodynia accompanying AGA patients compared to healthy controls could have a role in trichodynia.